GAYA ORANG TUA SEBAGAI PEMULUNG MENDIDIK ANAKNYA DIKELURAHAN DELIMA KECAMATAN TAMPAN – PEKANBARU - Rista Dewi Septiani Napitupulu Dewi Napitupulu; Sudirman '; Jaspar Jas Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: a formulation problems in this research is whether the parents as scavengers to educate children classified as good or not good. The purpose of this research is to know the parents as scavengers to educate children in the village of delima district tampan - pekanbaru. The benefits of this research is able to help and facilitate the improvement, especially the role of parents in educating their children. This study is descriptive approach the applicability. The population in this research is 30 people. You get the samples in this study uses techniques proportianate stratified random sampling.Instrument in a questionnaire that contains 50 items a statement. the parents as of educating children, as measured by indicators Authoritative (democracy), Authoritarlan (authoritarian), Permisive (permissive), Rijecting-neglecting (don't care). From the results of research note that the parents as scavengers educate their children in the village of delima district tampan - pekanbaru is quite good. Keyword: Style, Parents, Scavenger, Educate, Child